The Salmonella Specific, σE-Regulated, STM1250 and AgsA, Function With the sHsps IbpA and IbpB, to Counter Oxidative Stress and Survive Macrophage Killing - Hews, Claire L.; Pritchard, Emily J.; Rowley, Gary (Frontiers in Cellular and Infection Microbiology, 2019)
The host presents an array of environments which induce bacterial stress including changes in pH, antimicrobial compounds and reactive oxygen species. The bacterial envelope sits at the interface between the intracellular and extracellular environment and its maintenance is essential for Salmonella cell viability under a range of conditions, including during infection. In this study, we aimed to understand the contribution of the σH- and σE-regulated small heat shock proteins IbpA, IbpB, and AgsA and the putative σE-regulated stress response protein STM1250 to the Salmonella envelope stress response. Due to shared sequence identity, regulatory overlap, and the specificity of STM1250 and AgsA to Salmonella sp., we hypothesized that functional overlap exists between these four stress response proteins, which might afford a selective advantage during Salmonella exposure to stress. We present here new roles for three small heat shock proteins and a putative stress response protein in Salmonella that are not limited to heat shock. We have shown that, compared to WT, a quadruple mutant is significantly more sensitive to hydrogen peroxide, has a lower minimum bactericidal concentration to the cationic antimicrobial peptide polymyxin B, and is attenuated in macrophages.